SURFACE SMOOTHING OF THE SIDES OF PRISM-SHAPED BEECH WOOD DETAILS VIA LAPPING WITH FAST-ROTATING METAL CYLINDER (Innovation in Woodworking Industry and Engineering design, 2026)
The article presents and analysis the results from laboratory experimental researches over opportunity for effective surface smoothing of cutter-processed or initially sanded surfaces of prism-shaped steamed beech samples with grit number of a sandpaper № 80. The lapping is executed by a special work instrument – cylindrical steel circlet, loaded on the milling spindle. Upon handing over and further pressure of a detail to the smooth polished surrounding surface of the rotating bushing, the lapping that occurs results in smoothing of the detail’s surface that has been in contact. It is also due to the partial heating, densification, decrease and rounding of the tops of the microgrades remaining after sanding. The purpose of the research has been to evaluate the degree of smoothing, by checking the multiple influence of the major factors on which it depends. In this particular case, we have chosen to vary the following factors: feed speed of detail U; radially directed force of pressing to the spindle q; number of impacts over the same surface n. The research results show that a quality smoothing, equal to the traditional one that is double sanded with sandpaper №180 or №240, can be reached at values of the variable factors, as follows: u = 8÷10 m.min-1; q = 6÷8 kN.m-1; n = 1÷2 impact. Apart from the quality smoothing, this lapping method results in further economy of sandpaper and lacquer of up to 20%.